2018
DOI: 10.1210/jc.2018-00464
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Outcomes in Adults Born Preterm With Very Low Birthweight or Small for Gestational Age at Term: A Cohort Study

Abstract: The LBW groups and preferentially females in the VLBW group displayed a less favorable metabolic profile than did controls. The inverse association between MetS score and bone quality suggests enhanced future fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 1 publication
4
44
1
2
Order By: Relevance
“…Furthermore, other factors (ie, obesity, ageing, and physical inactivity) are also thought to be important in the timing of the onset and severity of the outcomes . As mentioned, epidemiological evidence suggests that low birth weight, a surrogate marker of prenatal undernutrition, predicts the increased risks of several cardiometabolic conditions later in life; these associations became stronger if low birthweight was combined with a high adult BMI, postnatal compensatory growth, or unhealthy lifestyle factors (ie, smoking, low physical activity, and poor diet), suggesting that the highest risks for cardiometabolic conditions were experienced by those with low metabolic capacity but high metabolic demand . Similarly, the findings of subgroup analyses indicated the potential mediation effects of certain factors in later life, showing that adjustment for age, alcohol, smoking, BMI, or physical activity attenuated or nullified the observed associations in some analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other factors (ie, obesity, ageing, and physical inactivity) are also thought to be important in the timing of the onset and severity of the outcomes . As mentioned, epidemiological evidence suggests that low birth weight, a surrogate marker of prenatal undernutrition, predicts the increased risks of several cardiometabolic conditions later in life; these associations became stronger if low birthweight was combined with a high adult BMI, postnatal compensatory growth, or unhealthy lifestyle factors (ie, smoking, low physical activity, and poor diet), suggesting that the highest risks for cardiometabolic conditions were experienced by those with low metabolic capacity but high metabolic demand . Similarly, the findings of subgroup analyses indicated the potential mediation effects of certain factors in later life, showing that adjustment for age, alcohol, smoking, BMI, or physical activity attenuated or nullified the observed associations in some analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the individuals are subsequently exposed to adequate nutrition or overnutrition in later life, these adaptive responses may increase susceptibility to the development of cardiometabolic conditions in adulthood . Indeed, epidemiological evidence has linked low birth weight, marker indicative of foetal undernutrition, to susceptibility to type 2 diabetes mellitus (T2DM), metabolic syndrome, hypertension, and coronary heart disease later in life. In addition to maternal and foetal nutritional status, low birthweight could also be an indicator of other prenatal factors, such as maternal age, obstetric complications, chronic maternal conditions, maternal body composition, smoking, pollution, and drug use .…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing full-text articles, seven articles without OR and/or 95% CI, four articles without relevant outcome, and three reviews were excluded. Finally, 15 published articles with 16 studies were included in this meta-analysis (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). All but two studies (20, 27) scored 7 points, and the remaining studies scored 5 or 6 points ( Table 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Many dietary, behavioral, and psychological factors have been confirmed to be associated with metabolic syndrome, such as sugar-sweetened and artificially sweetened beverage intake (10), low levels of physical activity and sedentary behavior (11), and anxiety (12). In recent years, many studies found an association of several perinatal risk factors, such as low birth weight (LBW) and premature birth, with the increased risk of metabolic syndrome, but some others showed contradictory results (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Therefore, this meta-analysis was conducted to evaluate the association of LBW and premature birth with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Prematurity has been associated with a poorer vascular growth, endothelial disfunction and less nitric oxide and elastin production 4 , resulting in arterial stiffness that may explain the risk of hypertension (HT) seen in preterm adults, regardless of genetic or environmental factors 5 . The association of HT with other risk factors also observed in preterm adults such as dyslipidaemia or insulin resistance 6 , result in an increased susceptibility to develop ischemic cardiopathy and cerebrovascular accident 7 . It has also been described in preterm patients an increased pulmonary vascular reactivity, resulting in cardiac remodelling leading to changes in structure and geometry of right ventricle 8 , associated with systolic and diastolic dysfunction 9,10 .…”
mentioning
confidence: 99%